Luwa: Entanglement in the Origin, Form, and Meaning of Balayan’s Oral Tradition - Belamide, Aidel Paul G. (Humanities Diliman: A Philippine Journal of Humanities, 2018)
This is an exploratory research on luwa, a poetic performance held in honor of a patron saint in Balayan, Batangas. It uses the concept of entanglement, as an alternative to hybridity, in showing the overlapping in the origin, form, and meaning of luwa due to integration of sociocultural contexts and influences. It aims to prove that a tradition resulting from postcolonial relations is better understood when seen as an historical outcome of intermingling of social groups, including those beyond the colonizer and the colonized, and of the diverging cultural complexes within the colonial and postcolonial societies. In this manner, the tradition is positioned within the wider context, the complexities of postcolonial condition are considered, and the dynamics among and within social categories are explored. Data was gathered through fieldwork conducted in Balayan in April and May 2014. Performances in several villages were observed, poems were collected, and the concerned individuals, including poets, priests, and the laity, were interviewed. Keywords: Entanglement, post colonialism, performance, oral tradition